Massive maxillary molars intrusion using indirect anchorage on TADs, case report - Luchka , Vasyl; Martyts, Yurii (Actual Dentistry, 2024)
Abstract. This study presents a comprehensive review of case focusing on the intrusion of maxіllary molаrs in individual necessitating prosthetic rehabilitation, incorporating a tailored treatment approach. Addressing the unique challenge of providing treatment without dіrect orthodontic supervision, especіally during extended periods such as the COVID-19 lockdown or for patients residing abroad, is a significant aspect. Furthermore, the study acknowledges the added complexity when the treatment timeframe may coіncіdes with the osteoіntegration process of dental implants. Using orthodontic miniscrew indirect anchorage, the study demonstrates the effectiveness of maxillary molars intrusion in solving various dental concerns, including restoring posterior occlusion and achieving occlusal clearance for prosthetic rehabilitation. Through the presentation of successful outcome in patient with overeruption and occlusal interference, the study highlights the simplified orthodontic procedures, preservation of tooth enamel, and maintenance of periodontal health achieved with this approach. Moreover, the study emphasizes the complementary role of mandibular molars space rehabilitation with dental implant prostheses in enhancing masticatory function and overall oral health, thus underlining the significance of skeletal anchorage systems in achieving predictable and stable results in complex dental cases. In conclusion, this study underscores the importance of interdisciplinary collaboration and innovative treatment approaches in addressing the challenges associated with maxillary molar intrusion for prosthetic rehabilitation. By incorporating personalized treatment strategies and utilizing orthodontic miniscrew indirect anchorage, the study provides valuable insights into achieving optimal outcomes and patient satisfaction in complex dental cases. Keywords: Maxillary molar intrusion, posterior occlusal rehabilitation, miniscrew, indirect anchorage, digital planning, intrusion plate